Effect of laser power during laser powder bed fusion on microstructure of joining interface between Tungsten and AISI 316L steel - Seung-Hoon Lee; Ji-Hoe Koo; Omer Cakmak; Jung-Wook Cho (Additive Manufacturing Letters)
This study investigates the deposition of tungsten (W) onto a 316L steel substrate by laser powder bed fusion (L-PBF), to optimize process parameters and analyze the interface between W and 316L. To obtain high-density W structure (98.89%), the optimal laser power was 350 W, and scan speed was 500 mm/s, but these parameters cause significant dilution of W in the W-316L interface; as a result, Fe7W6 intermetallics form, despite L-PBF being a non-equilibrium solidification process. These intermetallics which are brittle could degrade joint strength. By reducing laser power below 250 W, the dilution of W can be mitigated, and potentially minimize formation of intermetallics and increase joint stability for advanced manufacturing applications.